2016
DOI: 10.1242/jcs.180448
|View full text |Cite
|
Sign up to set email alerts
|

A tetraspanin regulates septate junction formation in Drosophila midgut

Abstract: Septate junctions (SJs) are membrane specializations that restrict the free diffusion of solutes through the paracellular pathway in invertebrate epithelia. In arthropods, two morphologically different types of septate junctions are observed; pleated (pSJs) and smooth (sSJs), which are present in ectodermally and endodermally derived epithelia, respectively. Recent identification of sSJ-specific proteins, Mesh and Ssk, in Drosophila indicates that the molecular compositions of sSJs and pSJs differ. A deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 38 publications
(34 reference statements)
5
95
0
1
Order By: Relevance
“…Among the 13 genes contained in this chromosomal region, we focused on one gene encoding a membrane protein, designated Tsp2A, because the Flybase indicated that it is highly expressed in the midgut and Malpighian tubules. Through immunological studies using the antibodies generated against a synthetic polypeptide corresponding to the C‐terminal cytoplasmic domain of Tsp2A, we found that Tsp2A exclusively localizes to sSJs in the midgut and Malpighian tubules …”
Section: Identification Of Ssj‐associated Proteins Using a Genetic Apmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 13 genes contained in this chromosomal region, we focused on one gene encoding a membrane protein, designated Tsp2A, because the Flybase indicated that it is highly expressed in the midgut and Malpighian tubules. Through immunological studies using the antibodies generated against a synthetic polypeptide corresponding to the C‐terminal cytoplasmic domain of Tsp2A, we found that Tsp2A exclusively localizes to sSJs in the midgut and Malpighian tubules …”
Section: Identification Of Ssj‐associated Proteins Using a Genetic Apmentioning
confidence: 99%
“…Immunolocalization studies revealed that the three membrane proteins Ssk, Mesh, and Tsp2A were exclusively located at sSJs in the midgut and Malpighian tubules of Drosophila (Fig. ) . Ssk consists of 162 amino acids and has four transmembrane domains.…”
Section: Molecular Structures and Functions Of Ssk Mesh And Tsp2amentioning
confidence: 99%
See 3 more Smart Citations